Assessment of dietary intake among adolescents with obesity according to the Guia Alimentar para a População Brasileira - Saied, Yasmin Hany; Filho, Ciro Pacheco de Mello; Filho, José Osmar Cardoso; Filizzola, Aline Peres Leite; Ganen, Aline de Piano; da Silva, Sandra Maria Chemin Seabra; Kobal, Priscila Sala (O Mundo da Saúde, 2026)
Obesity among adolescents is an increasing public health concern, with significant impacts. In this context, Fascicle 5 of the Guia Alimentar para a População Brasileira (GAPB), developed to guide healthy food choices among adolescents, was used as a reference in this study, which aimed to evaluate the dietary intake of adolescents with obesity, as well as to analyze its association with Body Mass Index (BMI). After approval by the Research Ethics Committee, 32 adolescents with obesity, aged between 13 and 19 years, were included. During the nutritional consultation, a 24-hour Dietary Recall (24hDR) was applied and anthropometric assessment (weight and height) was performed, with the data compared to the recommendations of Fascicle 5 of the GAPB. Statistical analysis was conducted using JAMOVI software. Of the 32 adolescents interviewed, 59.38% were female, with a median age of 15.4 years and a median BMI of 36.0 kg/m2. Among the adolescents, 46.88% were classified as having obesity and 53.12% as having severe obesity. A high frequency of consumption of ultra-processed foods (93.75%) and low intake of fruits (15.63%) and vegetables/legumes (43.75%) were observed. Breakfast consumption was reported by 87.50% of adolescents; those who did not consume breakfast had a higher median BMI (40.7 vs. 34.3), although without statistical significance. It was also observed that adolescents who did not consume beans had a significantly higher BMI (p = 0.042), as did those who consumed filled cookies and sweets (p = 0.036) or other ultra-processed foods (p = 0.026). The results indicate an association between the consumption of minimally processed foods, such as beans, and lower BMI values, whereas the intake of ultra-processed foods is associated with increased BMI. Therefore, it is essential to develop programs based on the GAPB that encourage healthy habits from adolescence, contributing to improved nutritional profiles and prevention of diseases in adulthood.